Degradation of Muscle Quality in Hybrid Grouper (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatu) Due to Oxidative Damage Caused by Ingestion of Oxidized Fish Oil - Yan, Xiaobo; Li, Zhihao; Dong, Xiaohui; Tan, Beiping; Pan, Simiao; Li, Tao; Long, Shuisheng; Huang, Weibin; Suo, Xiangxiang; Yang, Yuanzhi (Frontiers in Nutrition, 2022)
The aim of the study was to investigate the effects of fresh fish oil (FFO) and oxidized fish oil (OFO) diets on the muscle quality of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu). Hybrid grouper were fed with diets containing 9% FFO or OFO for 60 days. Muscle sample were collected at 0, 30, and 60 day and the selected indexes of muscle were measured. Malondialdehyde (MDA), reactive oxygen species (ROS), total cholesterol (TC) and triglycerides (TG) in grouper muscle accumulated gradually with prolonged ingestion time, especially OFO group. Total saturated fatty acids (ΣSAFA) was significantly reduced and total polyunsaturated fatty acids (ΣPUFA) was significantly increased of muscle in FFO group; meanwhile, the muscle ΣSAFA and monounsaturated fatty acids (ΣMUFA) contents in the OFO group were significantly higher than those in the FFO group and the ΣPUFA (especially C22:5n3, C22:6n3) contents was significantly lower than that in the FFO group at 60 d. Consumption of OFO diet for 60 d reduced the diversity of volatile compounds, significantly reduced the content of total esters and increased the content of total aldehydes and total aromatics in grouper muscle. Furthermore, ingestion of OFO diet significantly reduced the mRNA expression of fraction growth factors and antioxidant genes in the muscle of grouper. In conclusion, the increasing MDA content in FO and the oxidative rancidity of PUFA can cause the deterioration of grouper quality and flavor due to oxidative muscle damage.